PENINGKATAN DAYA SAING INDUSTRI KREATIF BERBASIS TEKNOLOGI INFORMASI DAN GOOD CORPORATE GOVERNANCE - Herry Laksito (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2021)
The purpose of this study is to examine the enhancement of the competitiveness of creative industries based on information technology and good corporate governance in Central Java. In this research, it is expected to find the right selection of information technology and the application of good corporate governance in an effort to improve the competitiveness of the creative industries in the handicraft sub-sector in Central Java. The sampling technique using purposive sampling method and get 112 respondents as samples that meet all the criteria. The analytical tool used to test the hypotheses in this study uses the Structural Equation Model. The results of this study indicate that it is necessary to utilize the development of information technology and the application of good corporate governance in an effort to increase the company's market competitiveness which will impact on improving company performance. In addition, transparency and accountability are also needed to build stakeholder's trust